BEHAVIORAL FINANCE INSIGHTS TO IMPROVE MANAGERIAL DECISION MAKING (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2025)
Behavioral finance provides a powerful lens for understanding how cognitive biases, heuristics, and emotional influences shape managerial decision-making. Traditional financial models assume rationality, yet managers frequently rely on intuitive judgments that deviate from optimal choices, creating inefficiencies in capital allocation, risk assessment, and strategic planning. This research examines key behavioral finance constructs—overconfidence, loss aversion, anchoring, herd behaviour, mental accounting, and framing effects—to analyze their impact on managerial decisions across corporate finance, investment evaluation, and organizational strategy. Using empirical datasets, experimental simulations, and behavioral scoring models, this study highlights how irrational tendencies affect forecasting accuracy, budgeting outcomes, and risk-taking patterns. Further, the study proposes an integrated Behavioral Insight Framework (BIF) using bias diagnostics, predictive analytics, and nudging mechanisms to guide managers toward more rational financial decisions. The findings demonstrate that incorporating behavioral finance insights leads to improved decision accuracy, enhanced risk management, and stronger strategic consistency. The study ultimately contributes to the development of behaviorally informed managerial policies that drive better organizational performance and financial stability.